'Amil al-Bi'ah al-Madrasiyyah 'Ala Takhthith at-Ta’lim li Mua’allim al-Lughah al-‘Arabiyyah - Rahmatillah, Ramadhani; Arifa, Zakiyah; Kholid, Nur (Institut Agama Islam Negeri Curup, 2023)
This research aimed to continue the previous research by describing Arabic language teachers’ lesson plans at MAN 2, MA Muhammadiyah, and MA Al-Umm in Malang, as these lesson plans were affected by the school environment. This research sought to describe the differences in lesson plans designed and implemented by Arabic teachers at the aforesaid schools. This research deployed a qualitative approach and the case study method with multiple case studies. The data were garnered from interviews and documentation. The research results showed differences in planning methods, bases, and sources of learning among these schools, which were caused by differences in the availability of teachers and systems at each school. The teachers planned to teach the Arabic language in MAN 2 based on KMA 183 using the joint method and group technique, while the Arabic language teacher in MA Muhammadiyah planned lessons based on the same report. The Arabic language teacher at MA Al-Umm planned lessons individually based on her own innovations. Therefore, each school should provide a supportive program to improve the competencies of the Arabic language teachers in planning lessons.